Simple Approach for Designing the Check Irrigation System - Chandra, Harish; Lohani, Umesh (Journal of Agricultural Engineering, 2005)
The experiment was conducted in loamy soil to evaluate the size of cheek basin for different available flow rates (14, 14.8, 17.5 and 23.8 1ps) for irrigating wheat crop. The graphical solution was developed to obtain the time of spread, optimum size of check basin, and time of water application for different values of infiltration rate (n = 0.2, 0.4, 0.6, 0.8 and 1.0) and depth of water application (5, 6 and 7 cm).